An Approach to Economic Rules through the Maxims of Fiqh - Tag al-Din سيف الدين إبراهيم (Journal of King Abdulaziz University: Islamic Economics, 2022)
This article aims to discuss the economic rule proposed by Zarqa to help distinguish Shariah-compliant financial debts from ribā-based debts with the aim of monitoring Islamic finance that mainly benefits Shariah-compliant debts. The article focuses on two main questions: (1) to what extent the Zarqa rule achieves the purpose for which it was designed and (2) whether or not Islamic finance needs other economic rules to better contain it in terms of economic performance, Shari’ah compliance and financial quality. This article highlights some aspects of Zarqa’s proposed rule that need to be examined more closely and concludes by proposing an alternative approach to economic rulemaking through economically-lodged fiqh maxims. This idea is particularly suited to the rule "kharāj bil-ḍamān", which opened up vast horizons of knowledge, with a scope that reached as far as the early European Renaissance. In order to propose this approach, it appeared necessary first to answer the fundamental question of what difference an economic rule is likely to make to existing Shari’ah criteria and ancestral fiqh maxims, as well as other related questions.